Germline MPL mutations may be a rare cause of “triple-negative” thrombocytosis - Borsani, Oscar; Pietra, Daniela; Casetti, Ilaria Carola; Vanni, Daniele; Riccaboni, Giacomo; Catricalà, Silvia; Grazia, Bossi; Boveri, Emanuela; Arcaini, Luca; Rumi, Elisa (Experimental hematology, 2024)
•Hereditary thrombocytosis is a rare inherited disorder•Germline MPL mutations may cause hereditary thrombocytosis•Non-canonical MPL mutation screening is crucial in triple-negative thrombocytosis Hereditary thrombocytosis (HT) is a rare inherited disorder with clinical features resembling those of sporadic essential thrombocythemia. This study included 933 patients with persistent isolated thrombocytosis for whom secondary reactive causes were excluded. Of 933 patients screened, 567 were JAK2-mutated, 255 CALR-mutated, 41 MPL-mutated, 2 double-mutated, and 68 were triple-negative. Two patients carried germline non-canonical mutations in exon 10: MPL W515* and MPL V501A. One triple-negative patient carried another germline non-canonical MPL mutation outside exon 10: MPL R102P. As germline MPL mutations may be underlying causes of HT, we recommend screening patients with triple-negative isolated thrombocytosis for non-canonical MPL mutations. Although clear evidence concerning HT treatment is still lacking, individuals with HT should probably be excluded from cytoreductive treatment. Thus, an accurate diagnosis is pivotal in avoiding unnecessary treatments.